Desain dalam Perspektif Hadis: (Studi Hadis Tematik) - Siti Salma; Muhammad Alif; Reva Hudan Lissalam (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Design in the perspective of Hadith encompasses not only visual and physical aspects but also incorporates moral, social, and spiritual values taught in Islam. In everyday life, Islam encourages its followers to create an orderly, clean, and beneficial environment and lifestyle in accordance with the teachings of Prophet Muhammad (peace be upon him). This study employs a thematic Hadith approach by collecting and analyzing Hadiths related to the theme of design, such as cleanliness, simplicity, beauty, social balance, and sincere intention. The Hadith sources used include authentic collections such as Sahih Bukhari, Sahih Muslim, and Sunan Abu Dawood. The findings reveal that design, according to Hadith, is a comprehensive effort to shape a life aligned with Islamic values, emphasizing ethics, usefulness, and balance between worldly life and the hereafter. Thus, the concept of design in Hadith is not merely a matter of aesthetics but also a form of worship that reflects noble character and brings individuals closer to Allah SWT.